Influence of atrial fibrillation on post‐discharge natriuretic peptide trajectory and clinical outcomes among patients hospitalized for heart failure: insights from the ASTRONAUT trial. (17th October 2016) - Greene, Stephen J.; Fonarow, Gregg C.; Solomon, Scott D.; Subacius, Haris P.; Ambrosy, Andrew P.; Vaduganathan, Muthiah; Maggioni, Aldo P.; Böhm, Michael; Lewis, Eldrin F.; Zannad, Faiez; Butler, Javed; Gheorghiade, Mihai; et al.
Abstract: Aims: Change in NT‐proBNP level is a common surrogate endpoint in early phase heart failure (HF) trials, but whether this endpoint is influenced by atrial fibrillation/flutter (AFF) is unclear. Methods and results: This analysis included 1358 patients from the ASTRONAUT trial, which randomized patients hospitalized for HF with EF ≤40% to aliskiren or placebo in addition to standard care. Patients were stratified by presence of AFF on baseline ECG. NT‐proBNP was measured longitudinally by a core laboratory at baseline, 1 month, 6 months, and 12 months. Compared with non‐AFF patients, AFF patients experienced greater reduction from baseline in log‐transformed NT‐proBNP (interaction P < 0.001), but this difference was not significant after adjustment (interaction P = 0.726). The ability of aliskiren to lower NT‐proBNP during follow‐up differed by AFF status (interaction P = 0.001), with aliskiren lowering NT‐proBNP more than placebo among non‐AFF patients only. After adjustment, baseline AFF was not associated with mortality or HF hospitalization at 12 months (all P ≥ 0.152). Conclusion: In this hospitalized HF cohort, AFF status did not influence post‐discharge NT‐proBNP trajectory or clinical outcomes after adjustment for patient characteristics. Aliskiren lowered follow‐up NT‐proBNP levels in patients without AFF, but had no influence among patients with AFF. This study generates the hypothesis that the ability of a HF trial to meet an NT‐proBNP defined endpoint may be influenced by the prevalence of AFF in the population. Because aliskiren did not improve outcomes in patients without AFF, this analysis suggests changes in NT‐proBNP induced by investigational therapies may be dissociated from clinical effects.